Novel Pseudomonas sp. SCA7 Promotes Plant Growth in Two Plant Families and Induces Systemic Resistance in Arabidopsis thaliana - Kuhl-Nagel, Theresa; Rodriguez, Patricia Antonia; Gantner, Isabella; Chowdhury, Soumitra Paul; Schwehn, Patrick; Rosenkranz, Maaria; Weber, Baris; Schnitzler, Jörg-Peter; Kublik, Susanne; Schloter, Michael; Rothballer, Michael; Falter-Braun, Pascal (Frontiers in Microbiology, 2022)
The diverse genus Pseudomonas is a well-known member of the rhizosphere and harbors many plant beneficial strains. Pseudomonas sp. SCA7, characterized in this study, was isolated from roots of the bread wheat Triticum aestivum. Sequencing and annotation of the complete SCA7 genome revealed that it represents a potential new Pseudomonas sp. with a remarkable repertoire for plant growth-promoting and biocontrol functions, including auxin (Indoleacetic acid, IAA) and siderophore production. In vitro and in planta experiments with the reference dicot plant A. thaliana and the original monocot host T. aestivum were conducted to identify the functional properties of SCA7. The isolate was able to colonize roots, to modify root architecture and to promote growth in A. thaliana as well as to increase plant fresh weight in T. aestivum under unchallenged conditions. Gene expression analysis revealed differential expression of genes involved in iron deficiency response and induced systemic resistance (ISR) in A. thaliana upon SCA7 inoculation, indicating a role of SCA7 in nutrient uptake and priming of plants. Moreover, confrontational assays of SCA7 with fungal and bacterial plant pathogens revealed growth restriction of the pathogens by SCA7 in direct as well as indirect contact, the latter indicating involvement of microbial volatile organic compounds (mVOCs) in these interaction. Gas chromatography-mass spectrometry (GC-MS) analyses revealed 1-undecene as the major mVOC, and octanal and 1,4-undecadiene as minor abundant compounds, in the emission pattern of SCA7. Additionally, SCA7 enhanced resistance of A. thaliana against infection with the plant pathogen Pseudomonas syringae pv. tomato DC3000, which could involve direct and indirect mechanisms. In line with these results, SA- and JA/ET-related gene expression in A. thaliana during infection with Pst DC3000 was upregulated upon treatment with SCA7, indicating the ability of SCA7 to induce systemic resistance. The thorough characterization of the novel Pseudomonas sp. SCA7 showed a remarkable genomic and functional potential of plant beneficial traits. These first results indicate that SCA7 is a promising candidate to be used as a biocontrol or a biostimulation agent for further studies including other plants and pathogens in large scale greenhouse experiments or field trials.